2015
DOI: 10.1016/j.celrep.2015.06.012
|View full text |Cite|
|
Sign up to set email alerts
|

Ets Factors Regulate Neural Stem Cell Depletion and Gliogenesis in Ras Pathway Glioma

Abstract: As the list of putative driver mutations in glioma grows, we are just beginning to elucidate the effects of dysregulated developmental signaling pathways on the transformation of neural cells. We have employed a postnatal, mosaic, autochthonous glioma model that captures the first hours and days of gliomagenesis in more resolution than conventional genetically engineered mouse models of cancer. We provide evidence that disruption of the Nf1-Ras pathway in the ventricular zone at multiple signaling nodes unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 55 publications
3
34
0
Order By: Relevance
“…Etv4 and Etv5 are well-known effectors of the FGF-Ras-ERK signaling cascade (Mao et al, 2009; Zhang et al, 2009; Hollenhorst et al, 2011; Li et al, 2012; Breunig et al, 2015). Moreover, ETV5 is specifically expressed in bRG among human cortical progenitor cells (Pollen et al, 2015; Thomsen et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Etv4 and Etv5 are well-known effectors of the FGF-Ras-ERK signaling cascade (Mao et al, 2009; Zhang et al, 2009; Hollenhorst et al, 2011; Li et al, 2012; Breunig et al, 2015). Moreover, ETV5 is specifically expressed in bRG among human cortical progenitor cells (Pollen et al, 2015; Thomsen et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The first plasmid constitutively expresses the pBase integrase enzyme (Figure 1A1. pBase catalyzes the random stable integration of plasmids that are flanked with piggyBac terminal repeats (PB TR) (Breunig et al, 2015; Chen and LoTurco, 2012). The second plasmid constitutively expresses a transactivator protein; the rtTA-V10 (tetON) transactivator protein is shown here (Figure 1A2).…”
Section: Basic Protocol 1: Cloning Of Respective Goi (Genetic Elementmentioning
confidence: 99%
“…For these reasons, investigation of gene function in these diverse contexts requires increasingly precise control over transgene expression. Further, pB-tet-GOI uses piggyBac transposition as a means of genomic integration of transgenic elements, allowing for the stable transduction of cell lineages through non-viral means (Breunig et al, 2015; Chen and LoTurco, 2012). Herein, we provide a detailed protocol for the use of the system in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Wiesner et al showed that the triple combination of NRAS‐G12V, EGFRvIII, and shp53 induced gliomas with 100% efficiency and median survival was 83 days. The piggyBac transposon system has been used to induce glioma with HRAS and AKT mutations . One limitation of the existing transposon‐based glioma models is that RAS mutations are rare in human gliomas; thus, there is a need for a highly penetrant glioma mouse model that genetically mimics human gliomas.…”
Section: Introductionmentioning
confidence: 99%